Correlating chemical and physical changes of photo-oxidized low-density polyethylene to the activation energy of water release. (December 2017) - Hirsch, Shiran Garnai; Barel, Boris; Shpasser, Dina; Segal, Ester; Gazit, Oz M.
Abstract: Understanding and quantifying the effect of degradation on the chemical and physical properties of LDPE films is crucial for maintaining high quality of recycled LDPE products. Thermal gravimetric analysis coupled with mass spectroscopy (TGA-MS), Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry and electron microscopy combined with modulated TGA (MTGA) were used to evaluate LDPE films that sustained natural and accelerated weathering. Cross-referencing the chemical changes occurring to the LDPE samples during the weathering process with the dynamic results of MTGA provided a strong correlation between the release of caged water from the bulk of the LDPE and a specific energy value ( E′ ), termed here as 'volitalization energy'. The E′ value and the temperature at which it is measured are shown, for the first time, to be descriptors for the extent of photo-degradation. The data for accelerated- and naturally-induced degradation show a similar trend with respect to the effect of UVA radiation. A strong correlation is shown between the extent degradation determined by the traditional carbonyl index and the rate of water evaporation at the E′ temperature. Highlights: The energy needed to remove water from the bulk of photo degraded LDPE is correlated to the extent of weathering. The activation energy of water volitalization from the bulk of the LDPE is defined. Modulated TGA is used to quantitatively measure weathering degree of phot degraded LDPE.